PENGARUH SHARED VALUE DAN WEB QUALITY TERHADAP ONLINE REPURCHASE INTENTION MELALUI TRUST SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA MAHASISWA UNIVERSITAS DIPONEGORO KONSUMEN LAZADA.CO.ID) - Muhammad Taufan R Prakoso; Naili Farida (Universitas Diponegoro, 2018)
This research is grounded by the widespread dissemination of internet technology along with its advancements, not only bringing a revolutionary impact on human life, but also the impact of real business operations. This phenomenon is characterized by the increasing number of internet users in the world from 2014-2018. Lazada Indonesia is a startup with the largest funding value in Southeast Asia. However, Lazada.co.id experienced sales decrease in the last 3 years in every sector. The purpose of this research is to know the effect of shared value and web quality towards online repurchase intention through trust as intervening variable. This type of research is explanatory research, with data collection techniques through questionnaires. The sampling technique used is purposive sampling technique. The sample in this study amounted to 100 respondents who are consumers of lazada.co.id. This research uses quantitative and SEM analysis techniques. SEM is used to analyze the relationship or the effect of independent variable to dependent variable that form a path. The result of the research shows that there is a positive effect of shared value variable to trust variable and web quality variable to trust variable. Based on hypothetical test by analyzing the regression weight, trust variable has a positive effect towards online repurchase intention variables. Thus, the variable trust can be said as a variable partial mediation.